Radiotherapy plus lenvatinib versus radiotherapy plus sorafenib for hepatocellular carcinoma with portal vein tumor thrombus: a retrospective study - Zhang, Min; Zheng, Zhuangzhuang; Ding, Qiuhui; Su, Jing; Xin, Ying; Jiang, Xin (Frontiers in Pharmacology, 2024)
Background & Aims: Portal vein tumor thrombus (PVTT) occurs frequently in hepatocellular carcinoma (HCC) patients. However, there is currently no satisfactory treatment. Radiotherapy (RT) and tyrosine kinase inhibitors (TKI) are currently commonly used. However, whether their combined use provides a survival benefit is debatable. This retrospective study compared the efficacy and safety between radiotherapy plus lenvatinib (RT+L) and radiotherapy plus sorafenib (RT+S) in the treatment of hepatocellular carcinoma with portal vein tumor thrombus (PVTT).Methods: Among patients with PVTT who received RT+L or RT+S between March 2017 and September 2022, the primary endpoints were overall survival (OS) and progression-free survival (PFS). The secondary endpoints were objective response rate (ORR), disease control rate (DCR), and incidence of treatment-related adverse effects.The prognostic factors were also assessed.The analysis included 152 patients (RT+L: 48; RL: 25; RT+S: 55; S: 24).Compared with the RT+S group, the RT+L group had a longer OS and PFS. Among patients with type I/II PVTT, the median OS times were 19.8 months and 13.5 months (P=0.047) and the median PFS was 12.3 months and 7.3 months (P=0.042), respectively.And the median OS of the patients with type I/II PVTT were 14.4 months and 8.3 months (P=0.030) and the median PFS was 8.3 months and 6.2 months (P=0.026). ORR and DCR in RT+L group (25.0% and 75.0%) were also little higher than those in RT+S group (20.0% and 70.9%), but not statistically significant. In univariate analysis, etiology, Type of PVTT, alpha-fetoprotein (AFP) level, Child-Pugh score, and treatment method influenced OS. Multivariate analysis confirmed that treatment method, etiology, alpha-fetoprotein (AFP) level, and Child-Pugh score were independent prognostic factors for OS. Similar safety profiles were observed in the RT+L and RT+S groups. The most common adverse events were myelosuppression, decreased liver function, fatigue, diarrhea, nausea, and vomiting. Most adverse reactions were grade 1-2.The side effects of radiotherapy plus lenvatinib were acceptable.Compared to RT+S, RT+L had good efficacy in the treatment of hepatocellular carcinoma with PVTT. Validation is needed in prospective studies with larger sample sizes.